2023
DOI: 10.3389/fdgth.2023.1181059
|View full text |Cite
|
Sign up to set email alerts
|

Examining perceptions of a telemedicine network for pediatric emergency medicine: a mixed-methods pilot study

Abstract: BackgroundUse of telemedicine for healthcare delivery in the emergency department can increase access to specialized care for pediatric patients without direct access to a children's hospital. Currently, telemedicine is underused in this setting.ObjectivesThis pilot research project aimed to evaluate the perceived effectiveness of a telemedicine program in delivering care to critically ill pediatric patients in the emergency department by exploring the experiences of parents/caregivers and physicians.MethodsSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…28 In a qualitative study of physicians who experienced an ED-based pediatric tele-resuscitation program, physicians found value in the ability of a telehealth provider to help integrate findings, communicate expectations, and address a local lack of trained staff-based partially on the reputation of the remote hospital providing tele-consultation. 29 Like our study, the authors identified the importance of collegial interactions, but consultations in their network were more frequent for medical consultation, rather than to facilitate administrative or technical aspects of care. A similar study in the Veterans Health Administration identified apprehension about the use of a new process as a potential barrier to use of an emergency tele-psychiatry program, but the perceived value of consultation was the most important factor driving telehealth use.…”
Section: Discussionmentioning
confidence: 57%
“…28 In a qualitative study of physicians who experienced an ED-based pediatric tele-resuscitation program, physicians found value in the ability of a telehealth provider to help integrate findings, communicate expectations, and address a local lack of trained staff-based partially on the reputation of the remote hospital providing tele-consultation. 29 Like our study, the authors identified the importance of collegial interactions, but consultations in their network were more frequent for medical consultation, rather than to facilitate administrative or technical aspects of care. A similar study in the Veterans Health Administration identified apprehension about the use of a new process as a potential barrier to use of an emergency tele-psychiatry program, but the perceived value of consultation was the most important factor driving telehealth use.…”
Section: Discussionmentioning
confidence: 57%